Studies on Schismatoglottideae (Araceae) of Bomeo II: Aridarum crassum, a new species from Sarawak, Malaysian Bomeo - Boyce, P.C; Wong, Sin Yeng (Singapore Botanic Garden, 2007)
Aridarum Ridl. is a genus consisting of nine species of rheophytic, sometimes facultatively lithophytic, forest herbs, are all endemic to Borneo. Previous work by Bogner & Hay (2000) recognised nine species of which one species was at that time inadequately known and thus not fully described. The species, treated as sp. A in Bogner & Hay (2000), was known from a single collection from the summit (850 m asl) of Gunung Gaharu (Sri Aman Division, Sarawak). Fieldwork by the second author at the same location, although at lower altitude (the summit is no longer accessible) resulted in three collections of what we believe to be the same species. This species is clearly distinguished from the rest of the genus Aridarum by the leaf laminae very stiffly coriaceous, glossy deep green adaxially and conspicuously raised punctate abaxially when fresh. We are hereby describing this novelty as Aridarum crassum S.Y.Wong & P.C.Boyce.